"Native Hut", Trinidad - (:unkn) unknown (Stephens Ltd., Trinidad, 2010)
A tapia hut nestled in a clearing amidst the beautiful greenery. The walls of tapia huts are made from a mixture of clay, grass, cow dung and water while the roof is made from carat or palm leaves. Printed on the reverse of the postcard: “This is a real photograph.”
Coloured (handpainted); Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Huts--Trinidad and Tobago; Dwellings--Trinidad and Tobago; Coconut palm--Trinidad and Tobago; Housing, Rural--Trinidad and Tobago; Wooden windows--Trinidad and Tobago; Thatched roofs--Trinidad and Tobago; Windows--Trinidad and Tobago; Ajoupa